Structural, Magnetic and Catalytic Properties of a New Vacancy Ordered Perovskite Type Barium Cobaltate BaCoO2.67. Issue 38 (1st June 2021) - Iqbal Waidha, Aamir; Khatoon Siddiqui, Humera; Ikeda, Yuji; Lepple, Maren; Vasala, Sami; Donzelli, Manuel; Fortes, A. D.; Slater, Peter; Grabowski, Blazej; Kramm, Ulrike I.; Clemens, Oliver
Abstract: A new vacancy ordered, anion deficient perovskite modification with composition of BaCoO2.67 (Ba3 Co3 O8 □1 ) has been prepared via a two‐step heating process. Combined Rietveld analysis of neutron and X‐ray powder diffraction data shows a novel ordering of oxygen vacancies not known before for barium cobaltates. A combination of neutron powder diffraction, magnetic measurements, and density functional theory (DFT) studies confirms G‐type antiferromagnetic ordering. From impedance measurements, the electronic conductivity of the order of 10 −4 S cm −1 is determined. Remarkably, the bifunctional catalytic activity for oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) is found to be comparable to that of Ba0.5 Sr0.5 Co0.8 Fe0.2 O3– y, confirming that charge‐ordered anion deficient non‐cubic perovskites can be highly efficient catalysts. Abstract : A new charge ordered oxygen deficient perovskite in barium cobaltate system is reported with bifunctional catalytic activity for oxygen reduction and oxygen evolution comparable to that to that benchmark perovskite catalyst BSCF.